2022
DOI: 10.1101/2022.03.05.483143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bessel-droplet foci enable high-resolution and high-contrast volumetric imaging of synapses and circulation in the brainin vivo

Abstract: Bessel beam has long been utilized in physics for its ability to maintain lateral confinement during propagation. When used for two-photon fluorescence microscopy, Bessel foci have enabled high-speed volumetric imaging of the brain. At high numeric aperture (NA), however, the substantial energy in the side rings of Bessel foci reduces image contrast. Therefore, a compromise between resolution and contrast has to be made, limiting Bessel foci in microscopy to low NA. Here, we describe a method of generating axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…More importantly, owing to the excellent resolution, contrast, and non-diffracting properties of the Bessel droplet, more sample details can be visualized by the Bessel droplet in contrast to the other two modalities. In contrast to the axially complementary Bessel droplets for achieving a continuous DOF, 41 the TEMP technique not only maintains the high-resolution and high-contrast merits but also allows the 3D reconstruction of sample volumes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…More importantly, owing to the excellent resolution, contrast, and non-diffracting properties of the Bessel droplet, more sample details can be visualized by the Bessel droplet in contrast to the other two modalities. In contrast to the axially complementary Bessel droplets for achieving a continuous DOF, 41 the TEMP technique not only maintains the high-resolution and high-contrast merits but also allows the 3D reconstruction of sample volumes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…1 , 0. 5 ( ) (1) where z target is the desired extension range and binarizes the normalized 3D 𝑏𝑖𝑛𝑎𝑟𝑖𝑧𝑒 𝐼 𝑥,𝑦,𝑧;𝑝 ( ) 𝑚𝑎𝑥 𝐼 𝑥,𝑦,𝑧;𝑝 ( ) ( ) , 0. 5 ( )…”
Section: Theory and Designmentioning
confidence: 99%
“…Recent work in tabletop multiphoton neural imaging has shown that wavefront engineering strategies using EDoF imaging and adaptive optics are powerful solutions to improve the imaging capability of neural imaging in-vivo [1,2]. To circumvent the need to headfix animals, the open source head-mounted Miniscope platform [3] is widely adopted for enabling high-resolution neural studies in freely behaving animals.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, several tabletop systems have demonstrated that EDoF imaging techniques can increase the access of neural imaging without the need for costly inverse algorithms 17 20 Typically, the EDoF capability is achieved by pupil engineering, which uses a custom component to modify the optical field as it passes through the pupil plane of a microscope. A large family of pupil functions have been shown to achieve an EDoF 19 , 21 …”
Section: Introductionmentioning
confidence: 99%